The Effect of Adsorbents on the Quality of Refined Eel Fish (Anguilla marmorata [Q.] Gaimard) Oil as a Raw Material for Pharmaceutical Preparations - Jamaluddin; Yuliet; Wa Ode S. Musnina; Yonelian Yuyun; Syahna Shaldan; S. Malasugi; Putri A. Arta; Gina N. Putri; Adetya Maryani; Muhammad F. Haq; Syamsul Lakahoro; Nurul Awwaliyah P. Firman; Siti B. Al-Amri; Sinta Amelia; Asriani Hasanuddin; Novalina Serdiati; Jusri Nilawati (Jurnal Penelitian Pendidikan IPA, 2024)
Eel fish (Anguilla marmorata (Q.) Gaimard) oil is a valuable source of health-promoting unsaturated fatty acids. Adsorbent selection during the bleaching stage of fish oil purification can significantly impact the final product quality.  This study aimed to evaluate the impact of different adsorbents on the quality of refined eel fish (Anguilla marmorata (Q.) Gaimard) oil. Eel fish oil was extracted using Soxhlet extraction with diethyl ether and purified through degumming, neutralization, and bleaching stages. Various adsorbents (bentonite, magnesol XL, and zeolite) were employed at different concentrations (1% bentonite, 3% magnesol XL, and 5% & 10% zeolite activated by acid and base) to remove impurities. The refined oils were analyzed for physical, chemical, and microbiological properties. Results showed that all adsorbents effectively improved the quality of eel fish oil, meeting most International Fish Oil Standard (IFOS) and Indonesian National Standard (SNI - 8467:2018) criteria. However, density and iodine values were below the specified limits. Microbiological analysis confirmed the absence of contamination, but lead levels exceeded the permissible standard.